2017
DOI: 10.1007/978-3-319-28832-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Computationally Efficient Boundary Element Methods for High-Frequency Helmholtz Problems in Unbounded Domains

Abstract: This chapter presents the application of the boundary element method to high-frequency Helmholtz problems in unbounded domains. Based on a standard combined integral equation approach for sound-hard scattering problems we discuss the discretization, preconditioning and fast evaluation of the involved operators. As engineering problem, the propagation of high-intensity focused ultrasound fields into the human rib cage will be considered. Throughout this chapter we present code snippets using the open-source Pyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 43 publications
0
43
0
Order By: Relevance
“…It has also been shown that different values of the coupling parameter can be chosen on different sections of the obstacle so long as its imaginary part is one-signed [33]; the ideas presented in this paper can equivalently be thought of as applying different values for the coupling parameter to different basis functions. [10,39]. The connection between these approaches and the Burton-Miller formulation is wellestablished, and it will be seen that the BIE proposed herein has strong similarities to some of them too.…”
Section: Non-uniquenessmentioning
confidence: 79%
See 4 more Smart Citations
“…It has also been shown that different values of the coupling parameter can be chosen on different sections of the obstacle so long as its imaginary part is one-signed [33]; the ideas presented in this paper can equivalently be thought of as applying different values for the coupling parameter to different basis functions. [10,39]. The connection between these approaches and the Burton-Miller formulation is wellestablished, and it will be seen that the BIE proposed herein has strong similarities to some of them too.…”
Section: Non-uniquenessmentioning
confidence: 79%
“…We remark that multiplication by implements a Dirichlet-to-Neumann map, since , and note that expressions like that for appear in the OSRC literature e.g. following (10) in [36].In the case where , becomes imaginary and the wave becomes evanescent, obeying a non-oscillatory exponential taper in the direction . The choice of whether follows the positive or negative imaginary branch of the square root is in some senses arbitrary, but we choose the positive branch because this makes physical sense.…”
Section: A Pressure Fieldmentioning
confidence: 92%
See 3 more Smart Citations